2014
DOI: 10.1152/ajpheart.00491.2014
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of type 5 adenylyl cyclase prevents β-adrenergic receptor cardiomyopathy: A novel approach to β-adrenergic receptor blockade

Abstract: Yan L, Vatner SF, Vatner DE. Disruption of type 5 adenylyl cyclase prevents ␤-adrenergic receptor cardiomyopathy: A novel approach to ␤-adrenergic receptor blockade. Am J Physiol Heart Circ Physiol 307: H1521-H1528, 2014. First published September 5, 2014; doi:10.1152/ajpheart.00491.2014.-␤-Adrenergic receptor (␤-AR) blockade is widely used to treat heart failure, since the adverse effects of chronic ␤-AR stimulation are central to the pathogenesis of this disease state. Transgenic (Tg) mice, where ␤-AR signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…14,15 We observed reduction of left ventricular mass following ERT in GAA-KO mice (Figure 1D), and the ratio of left ventricle mass to body weight was reduced to approximately 3.8, which is comparable to 3.0–3.5 of healthy mice. 16,17 However, propranolol administration prevented any reduction of left ventricular mass, in comparison with untreated GAA-KO mice (Figure 1D). The reduction of ventricular mass by ERT in Pompe mice was generalized, and not limited to the left ventricle, because the ratio of left ventricle mass to total ventricular mass was not changed by ERT, in comparison with untreated GAA-KO mice (not shown).…”
Section: Resultsmentioning
confidence: 91%
“…14,15 We observed reduction of left ventricular mass following ERT in GAA-KO mice (Figure 1D), and the ratio of left ventricle mass to body weight was reduced to approximately 3.8, which is comparable to 3.0–3.5 of healthy mice. 16,17 However, propranolol administration prevented any reduction of left ventricular mass, in comparison with untreated GAA-KO mice (Figure 1D). The reduction of ventricular mass by ERT in Pompe mice was generalized, and not limited to the left ventricle, because the ratio of left ventricle mass to total ventricular mass was not changed by ERT, in comparison with untreated GAA-KO mice (not shown).…”
Section: Resultsmentioning
confidence: 91%
“…There is accumulating evidence that increased oxidative stress is involved in the pathogenesis of various types of cardiomyopathy [ 88 ], including dilated [ 89 , 90 ], diabetic [ 91 , 92 ], ischemic [ 93 , 94 ], hypertensive [ 95 ], adriamycin-induced [ 96 ], and pressure overload-induced cardiomyopathy [ 97 99 ], as well as beta adrenergic receptor overexpression induced cardiomyopathy [ 3 , 100 ]. It is important to note that oxidative stress affects different cell types involved in cardiomyopathy, not just cardiac myocytes.…”
Section: Oxidative Stress In Cardiomyopathy and Heart Failurementioning
confidence: 99%
“…The AC5 KO model is also protected against cardiomyopathy and heart failure through oxidative stress mechanisms [ 3 ] (Figures 3 – 5 ). For example, chronic beta adrenergic receptor ( β -AR) stimulation induces cardiomyopathy and heart failure by increasing markers of oxidative stress damage including myocyte necrosis and apoptosis [ 100 ]. We found that augmenting oxidative stress by mating the AC5 KO mice with MnSOD KO mice resulted in loss of the protection against the decreased cardiac function and increased cardiac fibrosis in response to chronic catecholamine stimulation in the double knockouts ( Figure 5 ) [ 3 , 5 ].…”
Section: Oxidative Stress In Cardiomyopathy and Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…However, the overwhelming preponderance of data in patients support the concept that exercise improves not only healthy lifespan, but also longevity, as it clearly is protective against cardiovascular disease, diabetes, and obesity, all of which are known to reduce lifespan. As the AC5 KO mice exhibit longevity and protection against diabetes, obesity, and cardiovascular disease (Yan et al ., 2007, 2014; Lai et al ., 2013; Ho et al ., 2015) along with enhanced exercise performance demonstrated in the current investigation, this model replicates the human paradigm of healthful aging. Conversely, enhanced β adrenergic signaling results in diminished lifespan, not only in transgenic animal models, for example, overexpression of Gsα (Iwase et al ., 1996, 1997), but also in human aging studies with increased β2 adrenergic receptor genotype, where longevity is diminished (Zhao et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%